STRUCTURAL GEOLOGICAL ANALYSIS AND NATURAL FRACTURED BASEMENT RESERVOIR DISTRIBUTION AT KENANGA STRUCTURE BATANGHARI BLOCK, JAMBI SUB-BASIN, SOUTH SUMATRA - Manik Darmayanti, Dewi
Natural fractured basement reservoir has become an important exploration targets especially in the South Sumatra Basin since numerous wells showed strong evidence of hydrocarbons occurrences. Particularly in South Sumatra Basin where fractured basement reservoir contribute significant gas production. Hydrocarbon potential of natural fractured basement reservoir also becomes an exploration target in Batanghari Block which is part of Jambi Sub-Basin that is located on the northern slope of the South Sumatra Basin. Drilling result of Hari-1, Kenanga-1, Kenanga-2 and Kenanga-3 well, indicated the fact that not all wells in Kenanga structure showed the accumulation of hydrocarbons. Not all fractured basement develops reservoir. Hence, this study is aimed to understand the geological structures took place in the Kenanga structure and how the distribution of this fractured basement reservoir in the area in order to be developed into a significant gas field. The study was conducted by the interpretation of well data, especially image log data obtained from Kenanga-1 well to determine the fracture classification, fracture orientation, fracture density, aperture and fracture porosity combined with the interpretation of 2D seismic data. Palinspastic reconstruction is used to vi determine the sequence of the tectonic events that occurred in the area. Fractured modeling was conducted to determine the distribution of fractured basement reservoir in Kenanga structure. The result of this study revealed that the fractures created in the basement and Lower Pendopo Formation are caused by the contractional tectonic system which maximum stress has NE-SW direction. It took place at Pliocen-Pleistocen right after Muara Enim Formation was deposited. These structural patterns are resulting by strike slip movement which related with transpresional stress, and resulted the flower structures. The modeling results showed that the fracture will be concentrated in the area around or near the fault and also in the area of the maximum curvature. So the area near Kenanga-1 well is the area that has high fracture density.